The long-term effects of sales promotions on brand attitude across monetary and non-monetary promotions - Yi, Youjae; Yoo, Jaemee (Psychology & marketing, 2011)
This study compares the influence of sales promotions on brand attitude across promotion types over time. An experiment is conducted with 154 subjects, who are exposed to test materials for 12 weeks. Evidence shows that the long‐term effects of sales promotions on brand attitude vary across deal types. Non‐monetary promotions seem to work better in eliciting consumers' favorable brand attitude than monetary promotions over time. However, such effects are moderated by consumers' deal proneness. Although monetary promotions may induce more negative effects than non‐monetary promotions, these effects are weaker for high deal‐prone consumers than for low deal‐prone consumers. © 2011 Wiley Periodicals, Inc.